A STUDENT RESOURCE DEVELOPMENT MANAGEMENT: A MODEL OF PLANNING, ORGANIZING, LEADING AND CONTROLLING AT BUSTANUL ULUM BULUGADING BOARDING SCHOOL BANGSALSARI JEMBER - Halid, Ahmad (Jurnal Ilmu Manajemen (JIMMU), 2024)
This study aims to analyze and formulate human resource development strategies at the Pesantren Bustanul Ulum Bulugading Bangsalsari Jember using qualitative research methods and a phenomenological approach. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis techniques identify sources through books, papers and articles, magazines, online journals, and websites, etc. The results of the study indicate that human resource development at the Pesantren Bustanul Ulum Bulugading already has several human resource development strategies, namely a.) Preparation of comprehensive and measurable human resource development planning. b.) Increasing effective and efficient human resource development organization. c.) Development of a sustainable cadre and training system. d) Increasing the welfare and motivation of human resources. e.) Formation of a professional and Islamic work culture. These strategies are expected to help the Bustanul Ulum Bulugading Islamic Boarding School in developing quality and efficient human resources, so that they can improve the quality of education and achieve the institution's vision and mission.